CD28 Costimulation of T Helper 1 Cells Enhances Cytokine Release In Vivo - Langenhorst, Daniela; Haack, Stephanie; Göb, Selina; Uri, Anna; Lühder, Fred; Vanhove, Bernard; Hünig, Thomas; Beyersdorf, Niklas (Frontiers in Immunology, 2018)
Compared to naive T cells, differentiated T cells are thought to be less dependent on CD28 costimulation for full activation. To revisit the role of CD28 costimulation in mouse T cell recall responses, we adoptively transferred in vitro generated OT-II T helper (Th)1 cells into C57BL/6 mice (Thy1.2+) and then either blocked CD28-ligand interactions with Fab fragments of the anti-CD28 monoclonal antibody (mAb) E18 or deleted CD28 expression using inducible CD28 knock-out OT-II mice as T cell donors. After injection of OVA protein in adjuvant into the recipient mice we observed that systemic Interferon (IFN)γ release strongly depended on CD28 costimulation of the Th 1 cells, while secondary clonal expansion was not reduced in the absence of CD28 costimulation. For human memory CD4+ T cell responses we also noted that cytokine release was reduced upon inhibition of CD28 costimulation. Together, our data highlight the so far underestimated role of CD28 costimulation for the reactivation of fully differentiated CD4+ T cells.